Evaluation of effect of intravitreal injection bevacizumab in treatment of choroidal neovascualr membrane of the eye - Jethva, Jignesh J.; Gohil, Neepa R.; Parekh, Nilesh V.; Patil, Sandip D. (International Journal Of Community Medicine And Public Health, 2016)
Background: Age-related macular degeneration (ARMD) is the leading cause of irreversible blindness in individuals over 50 years in developed countries. The objective was to study the effect of intravitreal bevacizumab in patients of choroidal neovascular membrane of eye by visual acuity and fluorescence angiography photograph. Methods: Non-randomized, open label, prospective analysis of 30 eyes in 30 patients with choroidal neovascualr diagnosed by direct ophthalmoscope and slit lamp 90D biomicroscopy. Visual acuity of the clinically diagnosed patient was taken by ETDRS (early treatment diabetic retinopathy system) visual acuity chart. Fundus fluorescence angiography was done by topcon retinal camera. Now all patients regardless of type were given 3 injections of 0.05 ml of injection bevacizumab intravitreally at infratemporal site 3.5 mm and 4 mm away from the limbus in pseudophakic and phakic eye repectively at interval of 1 month. After 1 month of last dose, patient was assessed with ETDRS chart for visual acuity, FFA for anatomical changes. FFA was done before and after giving 3 injection of bevacizumab at monthly interval. Patients were asked for regular follow-up and patients were examined after 6 hours, 48 hours and 7 days for any early and late complications. Results: There was significant improvement of visual acuity after intravitreal bevacizumab treatment (before 1.196 log MAR and after 0.95067 log MAR with p value is 0.0001, paired t-test with t=6.333 with 29 degree of freedom) in cases of choroidal neovascular membrane. Gain in visual acuity was accompanied by a significant decrease in leakage in fluorescein angiography (FFA) Conclusions: We present evidence that intravitreal bevacizumab is an effective treatment for choroidal neovascular membrane.